Correlated ion analysis and the interpretation of atom probe mass spectra - Saxey, David (2011)
Several techniques are presented for extracting information from atom probe mass spectra by investigating correlations within multiple-ion detector events. Analyses of this kind can provide insights into the origins of noise, the shape of mass peaks, or unexpected anomalies within the spectrum. Data can often be recovered from within the spectrum noise by considering the time-of-flight differences between ions within a multiple event. Correlated ion detection, particularly when associated with shifts in ion energies, may be used to probe the phenomenon of molecular ion dissociation, including the questions of data loss due to ion pile-up or the generation of neutrals in the dissociation process.